2019
DOI: 10.1037/prj0000327
|View full text |Cite
|
Sign up to set email alerts
|

Enacting lived experiences: Peer specialists with criminal justice histories.

Abstract: Peer specialists are frequently employed in mental health settings, with growing evidence for positive impact on subjective aspects of recovery. As more individuals within the mental health system have criminal justice involvement, peer specialists with incarceration histories are increasingly important, yet little is known about how their experiences with the criminal justice system factor into their work. This study sought to understand the experiences of peer specialists with criminal justice histories and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…They offer day-to-day support for those released early from jail by accompanying them to initial probation meetings or treatment appointments and referring them to potential employers and landlords, helping people to negotiate and minimize continuing criminal sanctions and training professional staff on engaging consumers with criminal justice history [ 20 , 21 ]. PSWs with incarceration histories could successfully identify the liminal space in being supportive rather than providing support for the criminal offense, in contrast with the conventional methods that directly confront criminality [ 56 ]. In fact, having criminal history is the “critical component” for achieving recovery [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They offer day-to-day support for those released early from jail by accompanying them to initial probation meetings or treatment appointments and referring them to potential employers and landlords, helping people to negotiate and minimize continuing criminal sanctions and training professional staff on engaging consumers with criminal justice history [ 20 , 21 ]. PSWs with incarceration histories could successfully identify the liminal space in being supportive rather than providing support for the criminal offense, in contrast with the conventional methods that directly confront criminality [ 56 ]. In fact, having criminal history is the “critical component” for achieving recovery [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…PSWs with incarceration histories could successfully identify the liminal space in being supportive rather than providing support for the criminal offense, in contrast with the conventional methods that directly confront criminality [ 56 ]. In fact, having criminal history is the “critical component” for achieving recovery [ 56 ]. Multiple initiatives have been introduced to facilitate a reentry process for people recently released from incarceration, including Forensic Assertive Community Treatment, Assertive Community Treatment, Critical Time Intervention, and Women’s Initiative Supporting Health Transitions Clinic, through diverse community support groups involving PSWs [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research nondirective relationships and to support people to trust and engage with services. 12 Among people with substance use disorder, there is evidence that peer support can increase engagement with treatment, reduce relapse rates, improve relationships with providers and enhance treatment experience. 13 Peer support is also a fundamental component of trauma-informed care.…”
Section: Openmentioning
confidence: 99%
“…Previous research investigating experiential peer support in the forensic field has found that EPs feel they have a deeper understanding of the client's situation and the pain they are dealing with (Barrenger, Stanhope, and Atterbury 2017;Barrenger, Hamovitch, and Rothman 2019) and clients view them as non-judgmental (Matthews et al 2019;Thomas et al 2019;Buck 2018;Collica-Cox 2018). Several studies have found that both EPs and clients see EPs as role models (Collica-Cox 2018;Portillo, Goldberg, and Taxman 2017;Barrenger, Stanhope, and Atterbury 2017), although it is unclear whether EPs' lived experiences contribute to their credibility (Reingle Gonzalez et al 2019) or rather make them inauthentic (Buck 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that both EPs and clients see EPs as role models (Collica-Cox 2018;Portillo, Goldberg, and Taxman 2017;Barrenger, Stanhope, and Atterbury 2017), although it is unclear whether EPs' lived experiences contribute to their credibility (Reingle Gonzalez et al 2019) or rather make them inauthentic (Buck 2016b). It has also been shown that witnessing someone who has succeeded despite a problematic history can be inspirational and provide hope (Kavanagh and Borrill 2013;Marlow et al 2015;Portillo, Goldberg, and Taxman 2017;Buck 2014Buck , 2016bBuck , 2019Matthews et al 2019;Barrenger, Hamovitch, and Rothman 2019). In addition, studies have found that building a trusting relationship is important (Kavanagh and Borrill 2013;Matthews et al 2019;Barrenger, Hamovitch, and Rothman 2019;Thomas et al 2019) and that it may be easier for EPs to achieve this with clients due to their shared identity (Barrenger, Stanhope, and Atterbury 2017;Portillo, Goldberg, and Taxman 2017;Reingle Gonzalez et al 2019).…”
Section: Introductionmentioning
confidence: 99%